Triceps-to-Biceps Tendon Transfer for Restoration of Elbow Flexion in Brachial Plexus Injury - Weber, Morgan B.; Wu, Kitty Y.; Spinner, Robert J.; Bishop, Allen T.; Shin, Alexander Y. (The Journal of hand surgery (American ed.), 2025)
Restoring elbow flexion is a reconstructive priority in patients with brachial plexus injuries. This study aimed to evaluate the results and assess factors contributing to outcomes of triceps-to-biceps tendon transfer in patients presenting with delayed or chronic upper brachial plexus injury. Patients with traumatic brachial plexus injuries undergoing triceps-to-biceps tendon transfer at a single institution’s multidisciplinary brachial plexus center between 2001 and 2021 were retrospectively reviewed. The entire triceps tendon was transferred around the lateral aspect of the arm, secured to the radius with a tenodesis button, and reinforced with a side-to-side tendon transfer to the biceps tendon. Primary outcomes include the modified British Medical Research Council (mBMRC) elbow flexion strength and active elbow range of motion. Twelve patients (eight men and four women; mean age, 45.2 years) were included. The mean follow-up was 10.4 (range, 5–34) months. Nine patients achieved mBMRC ≥3. Five patients achieved mBMRC 4. Average active elbow flexion was 119°, with average extension deficit of 11°. There were three patients with unsatisfactory results, achieving mBMRC 2 elbow flexion. Triceps-to-biceps tendon transfer is an excellent tendon transfer option for restoring elbow flexion in certain patients with an adequately functioning triceps muscle, who present with a delayed or chronic brachial plexus injury. Although most patients achieved mBMRC ≥3 elbow flexion, there was an expected permanent loss of elbow active extension with a residual elbow flexion contracture. Therapeutic IV.